Government grants, plant survival and employment growth: a micro-econometric analysis - Sourafel Girma; Holger Görg; Eric Strobl (Institute for the Study of Labor (IZA), 2003)
In this paper we analyse the impact of governmental grant provision on plant performance. To this end we utilise rich information derived from three data sources for the manufacturing sector in Ireland, where grant provision has been an important part of the industrial policy. We use a matching technique combined with a difference-in-differences estimator in the empirical analysis. Our results indicate that particularly capital related, but also other types of grants can provide an important impetus to plant survival and employment growth. We also discover some differences in terms of the effectiveness of grants between foreign multinationals and domestic plants. Specifically, while grants have helped to stimulate employment creation in multinationals, they may not always be an effective way of ensuring that these remain in the host country. In contrast, grants have in general been successful in not only helping domestic plants to survive longer, but also to create more jobs.
Keywords: L2; H2; J2; 330; government assistance; grants; employment; survival; matching; difference-indifferences; Industriepolitik; Strukturpolitik; Subvention; Wirtschaftspolitische Wirkungsanalyse; Unternehmensentwicklung; Beschäftigungseffekt; Schätzung; Irland